2013
DOI: 10.1080/10255842.2011.618926
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of gastric ulcers based on the change in electrical resistance of acupuncture points using fuzzy logic decision-making

Abstract: Many theories of reflexology use ancient concepts which do not coincide with the modern medical terminology of anatomy, physiology and biophysics. This substantially reduces the trust of physicians in reflexology methods. During this research, several mathematical models for the interaction of the internal and biological active points of meridian structures have been proposed. The analysis of these models allows the specification of a list of gastric diseases for which reflex diagnostics and reflex therapy met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Thus far, many previous studies have been focused on the application of fuzzy modeling in early GI malignancy prognosis, risk assessment, and survivability prediction ( 14 , 22 , 23 , 49 ). Some of them demonstrated that applying fuzzy logic for CRC risk assessment can reduce diagnosis errors and disagreement among physicians at any level of prediction, prevention, and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, many previous studies have been focused on the application of fuzzy modeling in early GI malignancy prognosis, risk assessment, and survivability prediction ( 14 , 22 , 23 , 49 ). Some of them demonstrated that applying fuzzy logic for CRC risk assessment can reduce diagnosis errors and disagreement among physicians at any level of prediction, prevention, and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, a publication from Al-Kasasbeh et al [11] should be mentioned here. The analysis of mathematical models of the interaction of the internal and BAPs of meridian structures allows the specification of a list of gastric diseases for which reflex diagnostics and reflex therapy methods are most effective [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Another example shows that good results for the prediction and early diagnosis of diseases from the reaction energy of BAPs are obtained using complicated fuzzy logic decision making systems [10]. Last but not least, a publication from Al-Kasasbeh et al [11] should be mentioned here. The analysis of mathematical models of the interaction of the internal and BAPs of meridian structures allows the specification of a list of gastric diseases for which reflex diagnostics and reflex therapy methods are most effective [11].…”
Section: Discussionmentioning
confidence: 99%
“…Four studies using fuzzy logic were excluded. We determined that fuzzy logic is a technique that converts a linguistic variable, not a deep learning technique in itself (Kharal, 2009;Al-Kasasbeh et al, 2011;Al-Kasasbeh et al, 2012;Al-Kasasbeh et al, 2013). Studies on quality evaluation of herbs or traditional medicines were excluded because it was difficult to consider the use of CAM modalities (Tian et al, 2012;Wang et al, 2012;Tan et al, 2020).…”
Section: Study Selection Processmentioning
confidence: 99%